The Factors Related to Exclusive Breastfeeding among Working Mothers Based on the Theory of Becoming a Mother Approach - Krisnana, Ilya; Nastiti, Aria Aulia; Choirinidah, Ninik (International Journal of Psychosocial Rehabilitation, 2020)
Breast milk provides the best nutritional value for babies. Low intake of exclusive breast milk poses a threat to the growth and development of children. Most working mothers find dif iculties working and giving exclusive breastfeeding to their babies at the same time. This study aimed to analyze the exclusive breastfeeding factors among working mothers based on the theory of becoming a mother approach. This study used a descriptive analytic research design with a cross-sectional approach. The population of this study was working mothers who had infants aged 6-12 months. The total sample for this study was 90 respondents who met the inclusion criteria. The independent variables were infant temperament, social support, and maternal confidence. The dependent variable was exclusive breastfeeding. Instruments used in this study were the Infant Characteristics Questionnaire (ICQ), social support questionnaire, Maternal Confidence Questionnaire (MCQ) and exclusive breastfeeding checklist. The data were analyzed by using Spearmen rank correlation and regression logistic with a level of significance of α = 0.05 to determine the relationship between variables. The results showed that infant temperament had a negative correlation with exclusive breastfeeding. Social support had 2 subscales that correlated with exclusive breastfeeding which were emotional and informational support. Maternal confidence did not correlate with exclusive breastfeeding.